Breaching the Delivery Barrier: Chemical and Physical Airway Epithelium Disruption Strategies for Enhancing Lentiviral-Mediated Gene Therapy - McCarron, Alexandra; Farrow, Nigel; Cmielewski, Patricia; Knight, Emma; Donnelley, Martin; Parsons, David (Frontiers in Pharmacology, 2021)
The lungs have evolved complex physical, biological and immunological defences to prevent foreign material from entering the airway epithelial cells. These mechanisms can also affect both viral and non-viral gene transfer agents, and significantly diminish the effectiveness of airway gene-addition therapies. One strategy to overcome the physical barrier properties of the airway is to transiently disturb the integrity of the epithelium prior to delivery of the gene transfer vector. In this study, chemical (lysophosphatidylcholine, LPC) and physical epithelium disruption using wire abrasion were compared for their ability to improve airway-based lentiviral (LV) vector mediated transduction and reporter gene expression in rats. When luciferase expression was assessed at 1-week post LV delivery, LPC airway conditioning significantly enhanced gene expression levels in rat lungs, while a long-term assessment in a separate cohort of rats at 12 months revealed that LPC conditioning did not improve gene expression longevity. In rats receiving physical perturbation to the trachea prior to gene delivery, significantly higher LacZ gene expression levels were found when compared to LPC-conditioned or LV-only control rats when evaluated 1-week post gene transfer. This proof-of-principle study has shown that airway epithelial disruption strategies based on physical perturbation substantially enhanced LV-mediated airway gene transfer in the trachea.